2016
DOI: 10.1177/1557988316630770
|View full text |Cite
|
Sign up to set email alerts
|

Personal Descriptions of Life Before and After Bariatric Surgery From Overweight or Obese Men

Abstract: Bariatric surgery is now a common weight loss solution for morbidly obese men where meaningful weight reduction and improvements in quality of life have been identified postsurgery. As the majority of surgical candidates are female, there exists a paucity of literature relating to the experience of males undergoing bariatric surgery. In this study, a qualitative descriptive-exploratory design was used to explore body image descriptions, adaptation of a new lifestyle, new boundaries postsurgery, and any barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
2
27
0
4
Order By: Relevance
“…Recently, a study conducted by Lindekilde et al 41 to determine the effects of BS on body image found significant differences in recovery variables such as general body image, appearance evaluation, orientation, and body satisfaction between the pre-BS and post-BS third month time points. In concordance with our study, other studies [33][34][35][36][37][38] found positive changes in body image after BS. In some studies conducted on this subject, the effects of BS on QoL or body image were evaluated 3, 12, and 24 months after BS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, a study conducted by Lindekilde et al 41 to determine the effects of BS on body image found significant differences in recovery variables such as general body image, appearance evaluation, orientation, and body satisfaction between the pre-BS and post-BS third month time points. In concordance with our study, other studies [33][34][35][36][37][38] found positive changes in body image after BS. In some studies conducted on this subject, the effects of BS on QoL or body image were evaluated 3, 12, and 24 months after BS.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, from pre-BS to the post-BS 6, 12, and 24 months, it was found that body image and QoL improved with weight loss. 37 Similarly, in this study, it was found that the average of both body image and QoL scores increased from pre-BS to post-BS. In addition, in this study, linear regression analysis identified a relationship between body image and PF, RP, and RE of QoL.…”
Section: Discussionsupporting
confidence: 67%
“…Given that treatment‐seeking samples for obesity tend to include more women than men , it will also be useful to examine weight stigma in samples of men seeking treatment for obesity. Two recent qualitative studies of men seeking bariatric surgery for obesity have illustrated how gender may shape treatment experiences; for example, men noted surgery changed their self‐concept around masculinity, and male bariatric patients noted that information about the surgery procedure (e.g., recovery, patient experiences, health benefits) was largely geared toward women . Future research should also assess mechanisms that may drive gender differences in the weight stigma and health relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment of MO has focused essentially on diet, physical exercise or pharmacotherapy (Srivastava & Apovian, 2018), bariatric surgery has been shown to be a reliable method for weight loss and improving the quality of life on a physical, psychological and sexual level. As the majority of candidates for bariatric surgery are women, there is a scarcity of literature related to men's experiences of bariatric surgery (Edward, Hii, Hennessy, & Thompson, 2018). Although some studies have focused on men's experiences in bariatric surgery (Cohn, Raman, & Sui, 2019; Lynch, McGowan, & Zalesin, 2018), little is known about how they experience their sexuality.…”
Section: Introductionmentioning
confidence: 99%